Reducing Emissions through Low-Carbon and Biomaterials: The Case of Green Office Enjoy, Paris - Jolin Kaman; Eunike Kristi Julistiono (Advances in Civil Engineering and Sustainable Architecture, 2025)
Drastic transformation in the construction industry is required to achieve global net-zero targets while accommodating the continuing need to build to anticipate the growing population. With the increase implementation of energy efficient building, the significant of embodied carbon becomes higher. The use of biomaterial has great potential to reduce building emissions. This paper presents a case study that has been built with engineered timber components, and examines to what extent, a further reduction of embodied emissions can be performed. Three material replacements were proposed to further decarbonize the building emissions, and the embodied carbon reductions resulted by changing the timber specification and fly ash use in concrete mixture were assessed quantitatively with embodied carbon assessment. Results show that by replacing the building materials with lower carbon options, the embodied carbon of the case study can be reduced from 52 to 242 tons of CO2e or 2.82 to 12,99 kgCO2e/m2.